Prevalence of malaria parasites, Hepatitis B and C viral infections in pregnant women attending ante-natal clinic (Journal of Biomedical Investigation, 2008)
The prevalence of Hepatitis B virus (HBV), Hepatitis C virus (HCV) and malaria parasites (MP) was studied amongst pregnant women. One hundred pregnant women on routine visit to the ante-natal clinic were randomly recruited into the study. Analysis of their blood samples showed that 2(2%) out of the 100 pregnant women were sero- positive for HBV and 77(81%) out of 94 of pregnant women were positive for malaria parasites. However, all of the pregnant women were HCV sero-negative. The alanine amino transferase (ALT) values are not definitive for any particular infection. This study revealed that malaria parasites were the most prevalent infection among pregnant women. HBV infection in pregnant women is a cause for concern as it may result in congenital infection.
Keywords: Hepatitis B and C; Malaria; Pregnant women